Analisis perspektif generasi Z terhadap para bakal calon presiden pada pemilihan 2024 - Ahmaria, Siska (Maliki Interdisciplinary Journal, 2024)
As a democratic country, Indonesia regularly conducts general elections every 5 years. In 2024, there will be simultaneous elections in all regions of Indonesia. So who the next leader of Indonesia will be is determined by the people, and how people perceive the presidential candidates is very influential. The population that dominates Indonesia is generation Z. Generation Z can influence the culture and attitudes of the majority of people. Therefore, the author is interested in analyzing how generation Z perspectives on 2024 presidential candidates. This research was conducted qualitatively, which is an in-depth understanding of the phenomenon being studied from credible theories and sources. This research then produces findings that Gen-Z tends to vote for presidential candidates who do not have many conflicts on social media.